2022
DOI: 10.3390/ijms23094729
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Unstable and Elusive Plasmid That Encodes the Type III Secretion System Is Necessary for Full Virulence in the Marine Fish Pathogen Photobacterium damselae subsp. piscicida

Abstract: The marine bacterium Photobacterium damselae subsp. piscicida (Pdp) causes photobacteriosis in fish and important financial losses in aquaculture, but knowledge of its virulence factors is still scarce. We here demonstrate that an unstable plasmid (pPHDPT3) that encodes a type III secretion system (T3SS) is highly prevalent in Pdp strains from different geographical origins and fish host species. We found that pPHDPT3 undergoes curing upon in vitro cultivation, and this instability constitutes a generalized fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Additionally, it was also reported that Phdp secretes PnpA, a peptidoglycan hydrolase that can degrade the peptidoglycan of potential Phdp competitors [ 24 ], although the role of this protein in Phdp virulence remains unknown. In addition to these two factors, which are secreted by the type II secretion system (T2SS) of Phdp [ 24 , 25 ], it was recently reported that most isolates of Phdp harbor a type III secretion system (T3SS) [ 26 , 27 ], which is encoded in an unstable virulence-associated plasmid [ 28 ]. Although it is likely that the T3SS is involved in Phdp virulence, its specific functions remain undisclosed [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was also reported that Phdp secretes PnpA, a peptidoglycan hydrolase that can degrade the peptidoglycan of potential Phdp competitors [ 24 ], although the role of this protein in Phdp virulence remains unknown. In addition to these two factors, which are secreted by the type II secretion system (T2SS) of Phdp [ 24 , 25 ], it was recently reported that most isolates of Phdp harbor a type III secretion system (T3SS) [ 26 , 27 ], which is encoded in an unstable virulence-associated plasmid [ 28 ]. Although it is likely that the T3SS is involved in Phdp virulence, its specific functions remain undisclosed [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these two factors, which are secreted by the type II secretion system (T2SS) of Phdp [ 24 , 25 ], it was recently reported that most isolates of Phdp harbor a type III secretion system (T3SS) [ 26 , 27 ], which is encoded in an unstable virulence-associated plasmid [ 28 ]. Although it is likely that the T3SS is involved in Phdp virulence, its specific functions remain undisclosed [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…When a high‐efficiency transformation method is not available, an allelic exchange vector may be delivered by conjugation (Ferrières et al, 2010 ; Strand et al, 2014 ). To date, conjugative transfer of pir/RP4 suicide vectors from SM10/S17‐1 λ pir donor strains of Escherichia coli was the only method used to deliver the allelic exchange DNA in Pdp KO mutagenesis (Abushattal et al, 2022 ; Naka et al 2005 , 2007 ; Osorio et al, 2015 ). These donors contain the chromosomally integrated RP4::Mu conjugative transfer cluster (Simon et al, 1983 ), which was repeatedly shown to introduce off‐target mutations via Mu phage integration into the allelic‐exchange vector and/or the recipient's DNA, as well as Mu phage‐mediated and RP4‐mediated transfer and illegitimate integration of E. coli genes into the target host (Ferrières et al, 2010 ; Strand et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%